Pengembangan Media Pembelajaran Rumah Ludo Nusantara Pada Muatan Pembelajaran IPS Materi Keberagaman Budaya di Kelas IV Sekolah Dasar - Nabila, Ghalda; Sakmal, Juhana (Al-Azkiya: Jurnal Pendidikan MI/SD, 2025)
The Rumah Ludo Nusantara learning medium is going to be developed as part of this study with the intention of teaching Cultural Diversity to fourth-grade students in Social Studies. Experts in the fields of media, material, and language participated in the research, which was conducted using the research and development technique in conjunction with the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Additionally, the research was conducted on students in grade IV at SDN Paseban 18. 4 students participated in one-on-one testing, 8 students participated in small group testing, and 18 students participated in field testing. Data were collected using a quantitative descriptive approach, with evaluation scores of 92.18% from media experts, 93.75% from material experts, and 96.87% from language experts. Trial results showed average scores of 96.25% (one-to-one), 93.75% (small group), and 91.27% (field test). These findings indicate that Rumah Ludo Nusantara is highly suitable for use as a Social Studies learning tool on Cultural Diversity in grade IV.